1996
DOI: 10.1002/(sici)1096-9861(19960812)372:1<59::aid-cne6>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic input to mesial and superior area 6 in the macaque monkey

Abstract: The aim of the present study was to define the origin of the thalamocortical projections to each of the mesial and superior area 6 areas. To this purpose, restricted injections of neuronal tracers were made into areas F3, F6, F2, and F7 after physiological identification of the injection sites. The results showed that each of these areas receives afferents from a set of thalamic nuclei and that this set differs, qualitatively and quantitatively, according to the injected area. The main inputs to F3 [supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
68
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(83 citation statements)
references
References 122 publications
(255 reference statements)
14
68
1
Order By: Relevance
“…In general, the patterns of thalamocortical motor connections reported for macaques (e.g., Jones et al, 1979;Schell and Strick, 1984;Darian-Smith et al, 1990;Nakano et al, 1993;Shindo et al, 1995;Matelli and Luppino, 1996;Rouiller et al, 1999;Morel et al, 2005) are similar to those reported here for galagos. In both macaques and galagos, M1 receives dense inputs from VLp, less dense inputs from VLa, and only a few inputs from VM and VA. PMV receives dense inputs from medial VLp (area X), and less dense inputs from VLa, VM and MDmf.…”
Section: Thalamic Connections Of Motor Areas and Prefrontal Cortexsupporting
confidence: 90%
See 1 more Smart Citation
“…In general, the patterns of thalamocortical motor connections reported for macaques (e.g., Jones et al, 1979;Schell and Strick, 1984;Darian-Smith et al, 1990;Nakano et al, 1993;Shindo et al, 1995;Matelli and Luppino, 1996;Rouiller et al, 1999;Morel et al, 2005) are similar to those reported here for galagos. In both macaques and galagos, M1 receives dense inputs from VLp, less dense inputs from VLa, and only a few inputs from VM and VA. PMV receives dense inputs from medial VLp (area X), and less dense inputs from VLa, VM and MDmf.…”
Section: Thalamic Connections Of Motor Areas and Prefrontal Cortexsupporting
confidence: 90%
“…In macaques, inputs to SMA are dense from VLa and VLp, while a notable projection comes from MD (e.g. Matelli and Luppino, 1996), which was not seen in galagos.…”
Section: Thalamic Connections Of Motor Areas and Prefrontal Cortexmentioning
confidence: 94%
“…The cerebellar activation sites in lobule-VI were coactivated with pre-SMA and dPMC, as were the previously mentioned sites observed by Rees et al (1997). Anatomical connections between the cerebellum and dPMC and pre-SMA have been demonstrated in monkeys (Wiesendanger and Wiesendanger, 1985;Matelli and Luppino, 1996). Dorsal PMC and pre-SMA are involved in higher-order aspects of motor planning, and particularly the human dPMC has been shown to be involved in decision processes that precede motor output (Leonards et al, 2000;Peuskens et al, 2001).…”
Section: Role Of the Distinct Cerebellar Activation Sitessupporting
confidence: 70%
“…A significant correlation between activity in the dentate nucleus and SMA was similarly found by Liu and co-workers (1999) using a tactile discrimination task. Both M1 and SMA in monkeys have been shown to project to the cerebellum and to be the target of its transthalamic outputs (Rouiller et al, 1994;Matelli and Luppino, 1996;Hoover and Strick, 1999).…”
Section: Role Of the Distinct Cerebellar Activation Sitesmentioning
confidence: 99%
“…5). As predicted from literature from nonhuman primates (17,18,(33)(34)(35)(36)(37), connections from SMA were found to the corticospinal tract, precentral gyrus, and ventrolateral thalamus (Fig. 5 a and c), whereas connections from pre-SMA were found to the superior frontal gyrus, medial parietal cortex, inferior frontal cortex, and anterior thalamus (Fig.…”
Section: Resultsmentioning
confidence: 80%